Influence of Hot Consolidation Conditions and Cr-Alloying on Microstructure and Creep in New-Generation ODS Alloy at 1100 °C - Svoboda, Jiří; Luptáková, Natália; Jarý, Milan; Dymáček, Petr (Materials (Basel, Switzerland), 2020)
The coarse-grained new-generation Fe-Al-Y2O3-based oxide dispersion strengthened (ODS) alloys contain 5 vol.% homogeneously dispersed yttria nano-precipitates and exhibit very promising creep and oxidation resistance above 1000 °C. The alloy is prepared by the consolidation of mechanically alloyed powders via hot rolling followed by secondary recrystallization. The paper presents a systematic study of influence of rolling temperature on final microstructure and creep at 1100 °C for two grades (Fe-10Al-4Y2O3 and Fe-9Al-14Cr-4Y2O3 in wt%) of new-generation ODS alloys. The hot rolling temperatures exhibit a rather wide processing window and the influence of Cr-alloying on creep properties is evaluated as only slightly positive.
Keywords: creep; ODS alloy; consolidation via hot rolling; mechanical alloying; microstructure